Information security and cryptology : 12th International Conference, Inscrypt 2016, Beijing, China, November 4-6, 2016, Revised selected papers /: 12th International Conference, Inscrypt 2016, Beijing, China, November 4-6, 2016, Revised selected papers. (2017) - Unknown
No abstract available